STUDI EMPIRIS TENTANG PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi Pada Pengusaha Kena Pajak di KPP Pratama Semarang Barat) - Rachmawati Khoirina, 09.05.52.0041; ., Jaeni (Students Journal of Accounting and Banking, 2013)
This study aimed to analyze the influence of modernization of the tax administration system with variable modernization organizational structure, organizational procedures modernization, modernization strategy of the organization, and modernization of the organizational culture of compliance Taxable Person listed in the Tax Office Primary West Semarang. Population in this research is the Taxable listed in the Tax Office Primary West Semarang. Sample used in this study is 101 respondents with a sampling purposive sampling technique. Primary data collection method used was a questionnaire method. Analysis of data using multiple linear regression model. The results showed that: the modernization of the organizational structure, organizational procedures, organizational strategy, and organizational culture and a significant positive effect on adherence Taxable Person.Keywords: Taxable Tax Compliance, Modernization of organizational structure, Modernization of organizational procedures, Modernization of organizational strategy and Modernization of organizational culture.